Exploring the Nutritional Potential of Jatropha curcas on Body Metabolism: A Bibliometric Analysis - Elsa Yuniarti; Linda Rosalina; Davina Fitria (Frontiers on Healthcare Research)
Background: a natural source that has great potential as a source of antioxidants is Jatropha curcas (L.). This plant has attracted widespread attention due to its significant content of antioxidant compounds in various parts of the plant, including leaves, seeds, and roots. In addition to health benefits, Jatropha curcas also has applications in various fields, including body metabolism.